2018
DOI: 10.21037/jtd.2017.12.125
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of detecting circulating tumor cells and tumor cells in bronchoalveolar lavage fluid in diagnosis of peripheral lung cancer

Abstract: Detecting tumor cells in peripheral blood and BALF may sensitive to identify benign and malignant peripheral lung lesions and be of value for early diagnosis of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…In a subsequent study, Hur et al showed that BALF EV-based EGFR genotyping has an even better mutation detection rate than tissue/cytology-based typing and that its sensitivity increases with tumor stage, enabling researchers to follow the disease progression and potentially the response to treatment without burdensome repeat biopsies [ 107 ]. Lastly, an opportunity for the identification of lung cancer by BALF-derived liquid biopsy of cfDNA and tumor cells emerged [ 108 , 109 ]. Although research on the clinical usefulness of different components of a liquid biopsy from BALF is only just developing and is nowhere as advanced as similar research concerning blood, it is for sure reasonable and promising, since BALF enables the gathering of both cellular (CTCs) and noncellular components (cfDNA, EVs) directly from the tumor microenvironment, and it provides increased diagnostic sensitivity when compared to blood.…”
Section: Balf-evs As Biomarkersmentioning
confidence: 99%
“…In a subsequent study, Hur et al showed that BALF EV-based EGFR genotyping has an even better mutation detection rate than tissue/cytology-based typing and that its sensitivity increases with tumor stage, enabling researchers to follow the disease progression and potentially the response to treatment without burdensome repeat biopsies [ 107 ]. Lastly, an opportunity for the identification of lung cancer by BALF-derived liquid biopsy of cfDNA and tumor cells emerged [ 108 , 109 ]. Although research on the clinical usefulness of different components of a liquid biopsy from BALF is only just developing and is nowhere as advanced as similar research concerning blood, it is for sure reasonable and promising, since BALF enables the gathering of both cellular (CTCs) and noncellular components (cfDNA, EVs) directly from the tumor microenvironment, and it provides increased diagnostic sensitivity when compared to blood.…”
Section: Balf-evs As Biomarkersmentioning
confidence: 99%
“…The cut-off value of a CTC positive result was determined as CTC count ≥2, which has been published previously. 11 The upper limits of normality were 35 U/mL for CA125, 5 ng/mL for CEA, and 16.3 ng/mL for NSE.…”
Section: Methodsmentioning
confidence: 90%
“…7,8 This unique CEP8 + CTCs has been examined in a series of studies, which showed a significant association with diagnosis and/or prognosis of lung cancer with promising sensitivity and specificity. [9][10][11] According to the potential application of the CEP8 + CTCs on lung cancer management, this technique was utilized in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 1283 individuals belonged to the control groups, comprising healthy volunteers in 15 studies 13,[16][17][18][19]21,[23][24][25]27,28,[30][31][32][33] and patients with benign lung disease in 11 studies. 16,18,19,22,27,29,30,[32][33][34][35] Zhou et al 35 and Chen et al 18 included two cohorts and reported the sensitivities and specificities separately, referred to as Zhou QJ1 and Zhou QJ2, and Chen X1 and Chen X2, respectively ( Table 1). The characteristics of the included studies are displayed in Table 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Among the 21 trials published from 2009 to 2020, 17 studies enrolled patients from East Asian countries/areas (one from Japan and the remaining 16 from People's Republic of China), two studies were performed in the USA, one in Italy and one in France. Immunohistochemistry and immunofluorescence staining were used in 13 studies 13,19,21,22,[24][25][26][27][28][29]31,33,34 and polymerase chain reaction (PCR) identification methods were used in eight studies. [16][17][18]23,30,32,35,36 The count data for primary studies, including true positive (TP), false positive (FP), false negative (FN), and true negative (TN) results were extracted and presented in Table 1.…”
Section: Search Resultsmentioning
confidence: 99%